Gullies of two Hungarian regions - a case study - JakabGergely; Madarász, Balázs; Őrsi, Anna; Szalai, Zoltán; Kertész, Ádám (Hungarian Geographical Bulletin, 2011)
Gully erosion plays a decisive role in removing the fertile layer of the soil and it has an important long term effect in relief formation. The objective of this paper is to compare gully development and distribution in two pilot areas in Hungary and to reveal the factors controlling gully formation. The pilot areas are natural micro-regions, i.e. the Börzsöny Mountains and the Zselic hills. The results presented in this paper are based on the data of a nation-wide gully cadastre recently under compilation by the authors. The cadastre contains the gullies shown on digital maps (1: 10,000), gully lengths, mean gradients, land use and main properties of parent materials and soils. The results point to the development and formation of significantly different gullies in the pilot areas as a consequence of different environmental conditions. The most important result is the introduction of the concept of equivalent gully length characterizing the gullies of the given category. Topography is the main driving force in gully formation followed by land use type, parent rock and soil properties.